(4 * (-2) * 2) + (8 * (-2)) + (3 * (-2)) + 6 = -32
2006-10-23 05:46:33
·
answer #1
·
answered by DanE 7
·
1⤊
0⤋
Assuming 4(-2)2 in the above expression means "4 times negative 2 squared":
4(-2)2 + 8(-2) + 3(-2) + 6=
4 x 4 + -16 + -6 + 6=
16 + -16 + -6 + 6 = 0
2006-10-23 05:49:34
·
answer #2
·
answered by Jazz In 10-Forward 4
·
0⤊
0⤋
4(-2)2 + 8(-2) + 3(-2) + 6 = -16 - 16 - 6 + 6 = -32
2006-10-23 05:46:49
·
answer #3
·
answered by DavidK93 7
·
1⤊
0⤋
4(-2)2+8(-2)+3(-2)+6
-16-16-6+6=-32
2006-10-23 07:15:56
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
4(-2)2+8(-2)+3(-2)+6= -32
2006-10-23 05:48:29
·
answer #5
·
answered by CavemanCountry 1
·
0⤊
0⤋
if 4(-2)2 means product of 4 -2 and 2 ,then
-16-16-6+6 = -32
if 4(-2)2 means product of 4 (-2 )^2 ,then
16-16-6+6 = 0
2006-10-23 06:07:19
·
answer #6
·
answered by grandpa 4
·
0⤊
0⤋
The functionality f(x,y) = x^2 - xy - y is so as that: f(6,2) = 22 = 6 & 2, f(4,3) = a million = 4 & 3, f(8,2) = 40 six = 8 & 2, so 7 & 2 = 7^2 - 7 x 2 - 2 = 33, it somewhat is a answer (not sure this is the unique one)
2016-12-08 19:39:04
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
-32
Demonstrating:
[4x(-2)x2]+[8x(-2)]+[3x(-2)]+6=(-2)x[(4x2)+8+3]+6
as you see (-2) is common factor, then you have:
(-2)x[8+8+3]+6=(-2)x[19]+6=-38+6 therefore it equals to -32
I know there's much simpler methode (which i used in my head) but i wanted you to see the common factor.
Good luck :)
2006-10-23 05:47:52
·
answer #8
·
answered by American Wildcat 3
·
0⤊
0⤋
-32
2006-10-23 05:48:13
·
answer #9
·
answered by recovery 1
·
0⤊
0⤋
-32
2006-10-23 05:47:04
·
answer #10
·
answered by steve0stac 2
·
1⤊
0⤋